WTO Trade War Resolution for Japan's Chemical Export Restrictions to South Korea - Yordan Gunawan; M Fabian Akbar; Eva Ferrer Corral (Faculty of Law, Universitas Padjadjaran, 2022)
The research analyses the trade war between South Korea and Japan from the perspective of international law. The trade war involving South Korea and Japan was triggered by a decision by the Supreme Court of South Korea which ordered several Japanese companies to pay compensation to victims of Japanese forced labor during World War II. As a result, on July 1, 2019, Japan imposed restrictions on chemical exports to South Korea. South Korea accused Japan of violating international trade regulations concerning export restrictions. Therefore, South Korea took action by boycotting goods from Japan. The two countries resolved to remove each other from the whitelist of countries that obtain preferential trade status via their activities. The research method used is normative legal research with a case approach. The result shows that the trade war involving Japan and South Korea worsened bilateral relations. The World Trade Organization (WTO) carried out several mechanisms related to solving the problem, namely through consultation and conciliation involving the two countries, but it still needs to resolve the issue. It was also planned to establish a panel between South Korea and Japan by the WTO, but it has not been implemented until now and beyond the timeframe set by the WTO in establishing the Panel. Therefore, the study proposes that South Korea and Japan can initiate arbitration as a solution for another effort to resolve the problem because the arbitration mechanism obtains binding and final decisions.DOI: https://doi.org/10.22304/pjih.v9n3.a6